Selling happiness - Rodrigues, Ana Sofia Faustino (2017)
A thesis uncovering the conditions associated to the happiness seeking need. It starts with a scientific screening and characterization of happiness as a human condition, happiness as a need and formulates the evidences supporting the happiness seeking market. From here after, exploratory research tools are manipulated, to understand the Portuguese Happiness Seeker, its characteristics and potential, and best strategies are presented to be considered in the pursuit of happiness.